DIRECT CORRELATION OF STRUCTURE CHANGES AND THERMAL EVENTS IN HYDRATED LIPID ESTABLISHED BY SIMULTANEOUS CALORIMETRY AND TIME-RESOLVED X-RAY-DIFFRACTION - CHUNG, HS; CAFFREY, M (BIOPHYSICAL SOCIETY, 1992)
In many lipid systems, polymorphic and mesomorphic behavior depends on sample thermal history. To establish unequivocally the structural origin of endothermic and exothermic events in such systems, we have performed simultaneous calorimetry and time-resolved x-ray diffraction (SCALTRD). To this end, aluminum calorimetry crucibles were used to contain the hydrated lipid sample, and the calorimeter was mounted with the base of the crucible oriented perpendicular to a synchrotron-derived focused monochromatic x-ray beam for SCALTRD data collection. Measurements were made with hydrated monoelaidin and 1,2-dielaidoyl-sn-glycero-3-phosphoethanolamine (DEPE) contained in hermetically sealed crucibles. Time-resolved x-ray diffraction (TRXRD) data were collected using an x-ray image intensifier/video system and a streak camera containing an x-ray sensitive image plate and/or film. SCALTRD analysis of the lamellar gel to lamellar liquid crystalline phase transition in hydrated monoelaidin gives identical progress curves by calorimetry and TRXRD at a scan rate of 1-degrees-C/min. At faster rates, calorimetry shows a broader phase transition that starts at a lower and ends at a higher temperature than is observed by TRXRD. The disparity arises in part because the x-ray beam used in TRXRD interrogates only a small portion of the sample, whereas the calorimeter responds to the entire sample volume. Because data collection times are relatively long, radiation damage is an important potential problem for SCALTRD measurements. Such an eff ect was observed with DEPE/water in that TRXRD shows the lamellar gel to lamellar liquid crystalline phase transition occurring at a lower temperature than observed by calorimetry. We speculate that the sample accumulates impurities locally as a result of radiation damage that has the effect of lowering the phase transition temperature at the site of interrogation by the x-ray beam. This "methods-in-combination" SCALTRD approach facilitates the direct correlation of structure rearrangements and thermal events in the same sample under identical conditions of thermal history. The information content of the data so derived far surpasses that available from either method used in isolation.
Keywords: SYNCHROTRON RADIATION INVESTIGATIONS; DIFFERENTIAL SCANNING CALORIMETRY; SATURATED MONOACID TRIGLYCERIDES; LAMELLAR LIQUID-CRYSTAL; PHASE-TRANSITION; POLYMORPHIC TRANSITIONS; KINETICS; PHOSPHATIDYLETHANOLAMINE; MECHANISM; GEL